Trends and forecasts of vitamin A deficiency burden in China, 1990–2035 - Ye, Zhongming; Liu, Junping; You, Lijiao; Han, Yaoguo; Zhang, Xiaodan; Lei, Ming (Frontiers in Nutrition, 2025)
ObjectiveThe purpose of this study was to analyze changes in the disease burden caused by vitamin A deficiency (VAD) in China from 1990 to 2021, based on the Global Burden of Disease (GBD) Database, and to predict the disease burden trend in 2035 using the Bayesian age-period-cohort (BAPC) model.MethodsBased on modeled estimates from the GBD 2021 database, this study used Joinpoint regression to calculate annual percentage change (APC) and assess long-term trends (1990–2021) in VAD burden. Disaggregated analysis quantified the contributions of population growth, population aging, and epidemiological changes. The BAPC model was used to predict incidence, prevalence, and DALYs for 2035.ResultsFrom 1990 to 2021, VAD incidence and prevalence significantly declined across all age groups in China, most notably in children under 5 years (−6.23% average annual change). Disability-adjusted life years (DALYs) improved substantially for children and adolescents. However, DALYs rebounded among those aged 50–74 years. Significant age and sex disparities exist. Children under 5 years bear the heaviest burden. Women have a higher incidence and prevalence than men, while DALY rates are lower in men across all age groups. While overall trends in incidence and prevalence declined, DALYs showed recent increases. Decomposition analysis revealed that favorable epidemiological shifts primarily drove the decline in incidence and prevalence. Conversely, population aging increased the number of cases and DALYs. Projections for 2035 indicate continued declines in incidence, prevalence, and DALYs across all age groups. However, the rate of decrease is projected to be slower in middle-aged and older populations compared to younger groups.ConclusionThis study reveals the complex dynamics and shifting burden of VAD in China. It affirms past prevention successes while highlighting new challenges, particularly the increasing disease burden driven by population aging. To achieve “Healthy China 2030” goals, future strategies require a more refined, lifecycle approach focusing on vulnerable groups (children, pregnant women, and the elderly), strengthening surveillance and evaluation systems, and promoting research into pathogenesis and technological innovation to meet evolving public health needs.